Adenoidectomy versus mometasone furoate nasal spray in treatment of nasal obstruction in children due to adenoid hypertrophy: a comparative study - Pai, Vishwas K.; Shetty, Shravan S.; Devan, P. P.; Mahesh, S. G. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: One of the common causes for nasal obstruction in children is adenoid hypertrophy. It is common indication for surgical removal in these patients due to multiple morbidities. In severe symptoms adenoidectomy is recommended, however there are limitations for surgery like cleft palate.The safety of nasal steroid spray has been well reported. The aim of the current study is to determine the effectiveness of adenoidectomy verses mometasone nasal spray in treatment of children with adenoid hypertrophy. Methods: Randomized prospective study was conducted in the department of ENT on 60 children who met the inclusion criteria. They were randomized into 2 groups and pre-treatment scoring was accessed. Group A underwent adenoidectomy and Group B underwent mometasonefuroate nasal spray therapy. Patients were evaluated on 40th day, 4th month. Results: During the 40th day follow up post treatment, a significant difference was found with no nasal obstruction in 93.3% patients who underwent adenoidectomy compared to 63.3% for those treated with MF nasal. At follow up after 4 months, 93.3% patients in group A had had improvement in clinically as compared to 76.6% in group B were nasal obstruction was relived. In group A, there was significant reduction in adenoid grading after adenoidectomy compared to MF nasal spray at 40 days follow up (p≤0.001). However long term MF nasal spray also associated with significant reduction in the size. Conclusions: In patients were adenoidectomy is contraindicated, long term MF nasal spray treatment has good efficacy in treatment of nasal obstruction due to adenoid hypertrophy.